Nghiên cứu sự tạo thành và phân huỷ gốc tự do HO*, dưới tác dụng của xúc tác phức [Co(Acac)]+ - Huỳnh, Lê Văn; Thủy, Trương Thị; Hà, Trần Thị (Vietnam Journal of Chemistry, 2016)
Homogeneous catalysts complex is increasingly widely used in many fields. Under the catalytic effect of the complex, the reaction occurs in softer conditions, so the energy savings for the response process. Using the method, the inhibitor - competition, special effects with free radicals HO*, have demonstrated arising and destroying of free radicals HO*, under the effect of the catalytic complex [Co(Acac)]+, there is a change of oxidation of Co2+. Demonstrate, mechanism of reactions that take place under the original circuit. This paper is the research results arise and destroying the free radicals HO*, under the effect of the catalytic complex [Co(Acac)]+, has determined the reaction mechanism is the Circuit of radical and the oxidation rate constants k(Ind+HO*) = 5.46×108 (1.mol-1.s-1)